(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The food sector has seen a rapid increase in competition in the last decade due to changes in lifestyle and eating habits. Mobile food cart businesses are highly competitive due to their convenience and variety of common food. Mobile food carts are considered to be a high-profit food business idea due to their lower investment and better quality food at a lower price. Mobile food carts can also choose the location if their services do not seem to work well at a particular location. The popularity of mobile food carts has increased in recent years, with customers preferring quick service and high-quality products. This is due to the popularity of mobile food carts, which have become increasingly popular among restaurants and food brands. Mobile food carts can also be used as a marketing tool, as they can be used as a commercial kitchen and as an advertising tool to introduce a brand or product. When driving a mobile food cart in other places, it functions as a mobile banner for businesses. Regarding the Assessment of the Mobile Food Cart businesses to customer experience in terms of Fast Service, I strongly agree (3.54). Convenient was strongly agreed (3.33). In terms of meeting expectations vs reality, I strongly agree with 3.16. The cost of the product was agreed upon (3.25).Problems Encountered by the Respondents in Dining Mobile Food Carts. The first rank got 18% of the survey. Facebook got 72%. Respondents should try a different kind of experience in street foods. Mobile Food Cart owners must add more employees and equipment, give satisfaction to the customer, show customers how they prepare the food, how they make it fresh, have music and freshener, find other places that are not near roadways, implement a proper sanitizing, have other branches in different places, try to take part in all social media platforms.